Cavernous sinus thrombophlebitis of pregnancy: management dilemma in a Malagasy patient - RANDRIANANDRAINA, Patrick (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2020)
We report a case of infectious thrombophlebitis of the cavernous sinus in a pregnant woman, supported in the Malagasy medical context. It was a 15-week pregnant woman who has had a complicated form of facial acne. Paralysis of the right abducens nerve associated with a headache reinforced by a biological inflammatory syndrome made suspect a thrombophlebitis of the cavernous sinus. A hemoptysis associated limited the use of anti-thrombotic. Antibiotics by general means allowed signs to regress from the third day. The clinical and biological elements are crucial in the face of the contraindication and the unavailability of imaging examinations, which are necessary for diagnosis. Multidisciplinary follow-up is essential for a better prognosis of this complicated thrombophlebitis.